Flexible high-temperature sheet-type electric heaters using m-aramid/functionalized MWCNTs hybrid nanofiber composites. (1st June 2019) - Lei, Danyun; Ko, Tae Hoon; Yang, Jae-Yeon; Li, Xiang-Dan; Seo, Min-Kang; Kim, Hak-Yong; Kim, Byoung-Suhk
Abstract: Poly(m-phenylene isophthalamide) (m-aramid)/functionalized multi-walled carbon nanotube nanofibers (m-aramid/MWCNT-OH NFs) are prepared by electrospinning of the blended m-aramid/MWCNT-OH mixtures with MWCNT-OH contents of 0.1–1.0 wt%. Afterwards, the MWCNT-OH solutions (0.1–1.0 mg ml −1 ) dispersed in ethanol are further infiltrated into m-aramid/MWCNT-OH NF substrate via a facile solution casting method to obtain MWCNT-OH coated m-aramid/MWCNT-OH NF composites (MWCNT@m-aramid/MWCNT-OH NF composites). FE-SEM analysis demonstrates that the MWCNT-OH is well coated on the m-aramid/MWCNT-OH NF substrate, depending on the MWCNT-OH contents. The sheet resistance of as-fabricated MWCNT-OH@m-aramid/MWCNT-OH NF composites decreases largely from 2845 Ω □ −1 to 158 Ω □ −1 with the increase of MWCNT-OH concentrations from 0.1 to 1.0 mg ml −1, due to the percolation threshold of MWCNT-OH in the MWCNT-OH@m-aramid/MWCNT-OH NF composites. Besides, the obtained composites are flexible and reveal excellent electric heating performance. The maximum temperature of the MWCNT-OH(1.0 wt%)@m-aramid/MWCNT-OH NF composites is attained ca. 157 °C with high electric heating efficiency of 10.4 ± 1.8 mW/°C at small quantities (0.23 mg cm −2 ) of MWCNT-OH, suggesting that the MWCNT-OH(1.0 wt%)@m-aramid/MWCNT-OH NF composites can be applied as a promising high-temperature flexible sheet-type electric heaters. Graphical abstract: Image 1 Highlights: Flexible MWCNT-OH@m-aramid/MWCNT-OH nanofiber composites are prepared. The fabricated composites show excellent electric heating performance. High temperature sheet-like electric heaters with small quantities of MWCNT-OH.